The African American roots of modernism : from Reconstruction to the Harlem Renaissance - Smethurst, James Edward (University of North Carolina Press, 2011)
"In identifying the Jim Crow period with the coming of modernity, Smethurst upsets the customary assessment of the Harlem Renaissance as the first nationally significant black arts movement, showing how artists reacted to Jim Crow with migration narratives, poetry about the black experience, and more."-- Resumé vydavatele
Keywords: 19.-20. století; Afroameričané -- 19.-20. století; afroamerická kultura -- 19.-20. století; afroamerická literatura -- 19.-20. století; afroameričtí spisovatelé -- 19.-20. století; rasová segregace -- Spojené státy americké; modernismus (literatura) -- Spojené státy americké; Harlemská renesance; African American culture -- 19th-20th centuries; African American literature -- 19th-20th centuries; African American authors -- 19th-20th centuries; racial segregation -- United States; modernism (literature) -- United States; Harlem Renaissance; monografie; elektronické knihy; monographs; electronic books